Distribution of Yeast Cells, Temperature, and Fermentation By-Products in White Wine Fermentations - Schwinn, Mira; Durner, Dominik; Delgado, Antonio; Fischer, Ulrich (American Journal of Enology and Viticulture, 2019)
Yeast inoculation from the top of tanks is a usual practice in white wine fermentations. The objective of this study was to examine if inhomogeneities occur in tanks following yeast addition from the top with and without short stirring after inoculation. It was investigated if inhomogeneities affect fermentation kinetics and formation of acetaldehyde, acetic acid and pyruvate in Riesling juices with low turbidity. Samples and temperatures were taken at different tank heights in pilot-scale (105 L) and industrial-scale tanks (2500 and 7000 L) to investigate distributions of temperature, yeast and fermentation products in tanks of different volumes and height-to-diameter ratios. When yeast was not stirred in following inoculation, cell counts were higher in the upper tank section over the first days. Fermentation started earlier at the top of the tank as indicated by a lower specific gravity. From top to bottom, differences of up to 0.040 in specific gravity and up to 8.6°C in temperature were observed. Inhomogeneities lasted four days in 7000 L tanks. Results suggest slow yeast sedimentation and poor mixing in the downwards direction during pre-fermentation. During vigorous fermentation, all parameters were homogenously distributed. Short stirring after yeast inoculation provided uniform conditions during the pre-fermintation phase except for temperature differences which were due to natural stratification. Fermentation duration was shorter when yeast was stirred in. The final pyruvate concentration was significantly lower when the yeast was stirred in, presumably due to better nutrient availability throughout the whole tank, reducing SO2 demand. No differences were observed in acetaldehyde and acetic acid. When the yeast is not stirred in, sampling valves and temperature sensors of tanks do not reflect the whole tank during pre-fermentation which must be considered adverse for process contro
Keywords: fermentation dynamics; Saccharomyces cerevisiae; sedimentation; spatial distribution; white wine; yeast cell distribution

Entwicklung eines auf Referenz-Petri-Netzen basierenden hybriden Simulationstools zur wissensbasierten Reduzierung des Energie- und Wasserbedarfs bei der Weinerzeugung - Schütz, Martin; Schwinn, Mira; Hussein, Mohamed; Gatternig, Bernhard; Groß, Frauke; Durner, Dominik; Fischer, Ulrich; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
The objective of the research presented here was the development of a Reference-Petri Net-work-based hybrid simulation tool for the knowledge-based reduction of energy and water re-quirements in wine production. Data surveys on the water and electrical energy requirements, based on 1000 liters of the finished product, reveal deviations that in some cases significantly exceed the factor of 10. Using the developed simulation tool, winemaking processes in indi-vidual companies can be simulated and analysed for weak points. The hybrid tool uses Refer-ence-Petri-Nets as a structuring element. A developed basic structure enables the creation of a "virtual twin" of existing wine businesses as well as various calculations and output options for the individual processes by the user. Comparisons of different actions and expenditure of savings potential bring a new transparency into the overall process chain of winemakin
Keywords: Prozessvirtualisierung; Modellierung und Simulation; Energiemanagement; Referenznetze

Impact of fermentation temperature on required heat dissipation, growth and viability of yeast, on sensory characteristics and on the formation of volatiles in Riesling: Energy demand and volatiles during fermentation - Schwinn, Mira; Delgado, Antonio; Durner, Dominik; Wacker, Michael; Fischer, Ulrich (Australian Journal of Grape and Wine Research, 2019)
Background and Aims Temperature control during fermentation significantly impacts the energy demand of wineries. We determined the heat required to be dissipated from wine tanks under three different temperature programs (14, 16-11-17 and 19 degrees C) during 1200 L Riesling fermentations and investigated the influence of temperature on yeast growth and viability, the formation of yeast derived volatiles and wine sensory properties. Methods and Results Heat dissipated by the coolant was determined using heat meters. At 19 degrees C, similar to 70% less heat had to be dissipated compared to that at 14 degrees C, whereas similar to 30% less heat had to be dissipated for the 16-11-17 degrees C temperature program. The duration of fermentation was 15, 13 and 9 days for the 14, 16-11-17 and 19 degrees C programs, respectively. Characteristic profiles of heat dissipated per day and reduction in specific gravity were observed. The formation of most esters was more pronounced in the second half of fermentation at higher temperature. Hexyl acetate, however, was formed early and no temperature influence was observed. The final concentration of ethyl decanoate, ethyl octanoate and ethyl hexanoate was greater for fermentations at 19 degrees C, while that of ethyl butanoate was highest at 14 degrees C. No difference was found in the final concentration of acetate esters or acetic acid. Acetaldehyde concentration was 35% lower for fermentations at 19 degrees C, compared with those at 14 degrees C. Descriptive analysis, at 5 and 11 months after bottling, revealed no significant difference in wine sensory profiles. Flow cytometry showed faster yeast growth, greater population size and rapid viability decline at the higher fermentation temperature. Conclusions Energy savings can be achieved by reducing the required dissipated heat through temperature management of fermentations, without compromising wine composition. Ambient temperature should be considered when deciding on temperature management and related saving potentials. Significance of the Study Potential energy savings were demonstrated that may facilitate innovation in fermentation cooling systems.
CRIS-Team WoS Importer:2019-04-12
Keywords: energy saving; ester formation; fermentation; required heat dissipation; temperature management